ANALYSIS OF THE MAIN DUTIES AND FUNCTIONS OF THE JUDICIAL APPARATUS IN THE CIREBON DISTRICT COURT CLASS 1B IN IMPROVING THE EFFECTIVENESS OF PUBLIC SERVICES - Putri Salsabillah Nurfaidah; Moch Wildan Khaidar; Vanessa Yesika; Legian Dwi Ratsa (Jurnal Abdisci, 2025)
Abstract: Background. The District Court (PN), as a center for law enforcement and the provision of justice, plays an important role in the life of the community and the state. Good public services show public trust in legal institutions. Justice seekers expect excellent, transparent, and accountable service. Aims. This study aims to analyze the main duties and functions of the judicial apparatus in the Cirebon Class 1B District Court and its influence on the effectiveness of public services. The Cirebon Class 1B District Court, as one of the important institutions in the Indonesian judicial system, is required to provide public services effectively and efficiently. Methods. This study uses a normative legal research method, collecting data through literature studies and analyzing related documents. Result. The results of the study show that there is a compatibility between the main duties and functions of the judicial apparatus with the applicable laws and regulations and are expected to provide an overview of the extent to which the primary duties and functions of the judicial apparatus have run effectively and efficiently in organizing public services, as well as providing recommendations for improvement. Conclusion. This research is expected to contribute to efforts to improve the quality of public services in the Indonesian judiciary